PENGARUH KREDIBILITAS MEREK TERHADAP NIAT BELI KONSUMEN DENGAN VARIABEL DECISION CONVENIENCE SEBAGAI PEMEDIASI PADA MASKAPAI PENERBANGAN AIRASIA DI BANDA ACEH - Mulia Ulfa, Sorayanti Utami (Departemen Manajemen, 2017)
This study aims to determine the effect of brand credibility on consumer purchase intentions with variables decision convenience as mediators. The sample used in this study is 100 respondents who are customers of AirAsia airline Banda Aceh. Purposive Sampling is used as a sampling technique. Hierarcichal Linear Modeling (HLM) analysis method is used as an analytical method to determine the effect of the variables involved. The results of this study indicate that brand credibility has significant effect on purchase intention. In addition, the results obtained that the decision convenience variables partially influence the brand credibility to purchase intentions. The higher perceived brand credibility, the higher the decision convenience, the stronger the purchasing intention of the consumer.Keyword : Brand Credibility, Purchase Intention, Decision Convenience, AirAsia